2009
DOI: 10.1007/s11426-009-0102-3
|View full text |Cite
|
Sign up to set email alerts
|

Field-effect transistor chemical sensors of single nanoribbon of copper phthalocyanine

Abstract: Copper phthalocyanine (CuPc) nanoribbon field-effect transistors were implemented as chemical sensors. They showed fast response and high reversibility in the detection of the tetrahydrofuran atmosphere at room temperature. The drain current of the field-effect transistor sensor decreased from 6.7 to 0.2 nA when the transistor was measured under the tetrahydrofuran atmosphere. The sensor was self-refreshable in a few minutes. These results demonstrate that the organic single crystalline nanoribbon transistors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 26 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…In the past decades, 1D nanostructures of organic semiconductors [ 1,2 ] have attracted a great deal of research interest, due to their applications in miniaturized, multi‐functional photonic and electronic devices, such as optical waveguide, [ 3,4 ] nanolaser, [ 5–7 ] field‐effect transistor (FET), [ 8–10 ] photodetector, [ 11 ] and solar cell. [ 12,13 ] Noncovalent self‐assembly of molecular building blocks driven by ππ stacking and/or hydrogen bonding is one of the simplest methods to fabricate 1D organic nanostructures.…”
Section: Figurementioning
confidence: 99%
“…In the past decades, 1D nanostructures of organic semiconductors [ 1,2 ] have attracted a great deal of research interest, due to their applications in miniaturized, multi‐functional photonic and electronic devices, such as optical waveguide, [ 3,4 ] nanolaser, [ 5–7 ] field‐effect transistor (FET), [ 8–10 ] photodetector, [ 11 ] and solar cell. [ 12,13 ] Noncovalent self‐assembly of molecular building blocks driven by ππ stacking and/or hydrogen bonding is one of the simplest methods to fabricate 1D organic nanostructures.…”
Section: Figurementioning
confidence: 99%
“…It is found that the gas-sensor performance of MPc strongly depends on its microstructure [19][20][21]. For example, copper (Cu) Pc nanoribbons based gas sensor showed high reversibility and response to tetrahydrofuran atmosphere [22]. Poly-Cu tetraaminoPc nanotubes as the sensor exhibited fast sensitivities and enhanced linear ranges [23].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of nanoscience and nanotechnology, considerable attention has been focused on nanosized phthalocyanine owing to its unique properties and promising applications. Such as photovoltaic cell [2][3][4], chemical sensors [5], light-emitting diodes [6], organic field effect transistors [7][8], microelectronics [9] and photocatalysis [10][11][12].…”
Section: Introductionmentioning
confidence: 99%